2005
DOI: 10.1111/j.1471-4159.2004.02940.x
|View full text |Cite
|
Sign up to set email alerts
|

Axonal transport of the cellular prion protein is increased during axon regeneration

Abstract: The cellular prion protein, PrP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Studies have suggested that glial cells do not express PrP C , as it could not be detected following axon degeneration with Schwann cells still present (Moya et al, 2005). In contrast PrP C expression in glial cells (Moser et al, 1995) and specifically myelin of the CNS has previously been reported (Mironov et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Studies have suggested that glial cells do not express PrP C , as it could not be detected following axon degeneration with Schwann cells still present (Moya et al, 2005). In contrast PrP C expression in glial cells (Moser et al, 1995) and specifically myelin of the CNS has previously been reported (Mironov et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Of particular note, after intraocular injection in chick embryos, endogenous or exogenous recombinant PrP c are reported to be internalized by retinal ganglion cells and then anterogradly conveyed within axons in the direction of the optic tectum (Butowt et al 2007). This highlights the driving force behind PrP c for functional destination towards the growth cone in developing axonal fibers (Moya et al 2005) or axonal synapses in the mature neuron (Borchelt et al 1994). PrP c can also use retrograde transport for escorting informative molecules to the cell body (Moya et al 2005).…”
Section: Discussionmentioning
confidence: 96%
“…This highlights the driving force behind PrP c for functional destination towards the growth cone in developing axonal fibers (Moya et al 2005) or axonal synapses in the mature neuron (Borchelt et al 1994). PrP c can also use retrograde transport for escorting informative molecules to the cell body (Moya et al 2005). In addition to a constitutive localization on the postsynaptic side (Moya et al 2000;Bailly et al 2004), PrP c might occupy this site by transynaptic migration after being freely released (Moya et al 2000;Liu et al 2002) or associated with exosomes (Fauré et al 2006).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have recently reported a functional characterization of this transgenic line showing that overexpression of ERp57 improves recovery in peripheral nerve regeneration after mechanical injury to sciatic nerve (57), indicating that the overexpressed chaperone is functional in the nervous system. Interestingly, PrP expression is induced in models of peripheral nerve degeneration (68), and its deficiency triggers myelin defects (69). Because mice overexpressing ERp57 displayed augmented levels of PrP in the nervous system, it remains to be determined whether part of the beneficial effects of overexpressing ERp57 are due to enhancement of PrP expression.…”
Section: Discussionmentioning
confidence: 99%